1990
DOI: 10.1093/jee/83.3.883
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Attraction of Four Different Fiberglass Traps to Various Age and Sex Classes of Stable Fly (Diptera: Muscidae) Adults

Abstract: An Alsynite cylinder trap and three different Williams cross-configuration traps with three adhesives were compared to determine their relative attraction to stable fly, Stomoxys calcitrans (L.), adults. Williams traps coated with Olson Sticky Stuff performed as well as Williams traps coated with Tack Trap, thus allowing fly samples collected with either adhesive to be compared. The cylinder trap captured fewer total flies, but more flies per cm2 than any of the Williams traps. Sex ratio of flies captured on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
1
16
2
1
Order By: Relevance
“…These traps were biased toward males by a ratio of Ϸ2:1. This differs from Hogsette and Ruff (1990) who found the sex ratio to be closer to 1:1 on cylindrical traps compared with 1:2 on Williams (1973) traps. The physiological status of the collected ßies was similar among the sticky traps as well.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These traps were biased toward males by a ratio of Ϸ2:1. This differs from Hogsette and Ruff (1990) who found the sex ratio to be closer to 1:1 on cylindrical traps compared with 1:2 on Williams (1973) traps. The physiological status of the collected ßies was similar among the sticky traps as well.…”
Section: Discussioncontrasting
confidence: 88%
“…Also, the sleeves used with the Olson traps were much thinner than the Sur-Flex sleeves used for the Broce traps; and Þnally, the Olson trap sleeves were preglued, whereas Tangle-Trap was used on the Broce traps. Previous studies have noted signiÞcant effects of the types of glue and sleeves used on Alsynite traps on the number of ßies collected (Pickens andHayes 1984, Hogsette andRuff 1990). We observed that ßies were more difÞcult to remove from the Olson traps than the Broce traps.…”
Section: Discussionmentioning
confidence: 50%
“…This is similar to the 50% males caught by Hogsette and Ruff (1990) on four Florida dairy farms but different from the 61% males caught by Guo et al (1998) in a cattle feedlot. Both of these used Alsynite traps.…”
Section: Hourly Captures By Coroplast and Alsynite Trapssupporting
confidence: 39%
“…stable ßy populations by using Alsynite traps (Berry et al 1986, Mullens and Meyer 1987, Broce 1988, Thomas et al 1989, Lysyk 1993, Berkebile et al 1994, Guo et al 1998, Cilek 1999. Hogsette and Ruff (1990) found that Williams traps Þtted with plastic sleeves caught about half as many stable ßies as traps with directly applied adhesive. We observed even greater effect of choice of adhesive on catch (Table 3).…”
Section: Comparison Of Coroplast Card Alsynite Card Andmentioning
confidence: 99%
“…Three traps were placed similarly on all farms, with one trap near pastured horses, a second near barns with stabled horses, and a third near composting or manure spreading areas. Each trap was set up similarly to those described previously (Williams andRogers 1976, Hogsette andRuff 1990), with a trap height of 90 cm. The translucent adhesive-coated propylene sleeves (Olson Products Inc.) were replaced weekly, allowing stable ßy numbers to be recorded.…”
Section: Methodsmentioning
confidence: 99%